Information Resource Management: the Organisations’ Need for a Secure Approach - Bhattacharyya, Amitava (Journal of Information and Knowledge, 2010)
Organizations need to maintain their digital knowledge base in a controlled environment with provisions for conditional access. Along with its trademark efficiency of use, digital information resource management brings potential security concerns which need to be systematically apprehended and addressed. Creation and implementation of information security policies are essential to combat these vulnerabilities.